PENGEMBANGAN PABRIK GULA BANJARATMA SEBAGAI HERITAGE REST AREA: PERSEPSI TERHADAP NILAI-NILAI PENTINGNYA - Alya, Hasna; Ginanjar, Agi (Multikultura, 2025)
The Banjaratma Heritage Rest Area is a form of development of the Banjaratma Sugar Factory with the concept of adaptation and revitalization. Until it was inaugurated as a rest area in 2019, the Banjaratma Sugar Factory still had the status of an Alleged Cultural Heritage Object (ODCB). This research reviews the suitability of the form of adaptation and revitalization of the Banjaratma Sugar Factory to UU No.11 of 2010 concerning Cultural Heritage and the perception of the significant values of the Banjaratma Sugar Factory. The method used is an archaeological research method, includes seven steps, including formulation, implementation, data collection, data processing, analysis, interpretation and publication. The aim of this research is to show changes in the Banjaratma Sugar Factory from time to time through the implementation of adaptation, revitalization and compliance with the Cultural Heritage Law, as well as explaining the influence of the development of the Banjaratma Sugar Factory on the significant values that have been identified. This research proves that the form of adaptation and revitalization of the Banjaratma Sugar Factory is in accordance with the principles of the Cultural Heritage Law. Of the 99 respondents consisting of administrators, sellers and visitors, the majority strongly agreed or agreed that the Banjaratma Heritage Rest Area has significant value for history, knowledge, education, culture, social and economics. The community's positive perception of these significant values shows that the development of the Banjaratma Sugar Factory through adaptation and revitalization has not caused a decline in its significant values.